The role of laparoscopy in paediatric and adolescent gynaecology - Aleksandra Raźnikiewicz; Wojciech Korlacki; Andrzej Grabowski (Videosurgery and Other Miniinvasive Techniques)
Paediatric and adolescent gynaecology is a narrow field of medicine dealing with the diagnosis of and treatment of gynaecological diseases from the neonatal period to sexual maturity. The current trend in surgical gynaecology in the paediatric population is to minimise the degree of invasiveness of diagnostic and therapeutic procedures. This contributes to reducing the number of complications and the risk of infertility. Laparoscopic procedures are a challenge for paediatric surgeons and gynaecologists, not only because of the age of treated patients, and anatomical and physiological differences between different age groups but also because of the complexity of the pathology, the differentiation of cancer tumours, and the presence of congenital developmental defects.